Development of a Porcine VCA Model Using an External Iliac Vessel-Based Vertical Rectus Abdominus Myocutaneous Flap - Blades, Caitlin M.; Greyson, Mark A.; Dumanian, Zari P.; Yu, Jason W.; Wang, Yong; Li, Bing; Wang, Zhaohui; Washington, Kia M.; Huang, Christene A.; Navarro-Alvarez, Nalu; Mathes, David W. (Journal of Reconstructive Microsurgery, 2024)
Background Vascularized composite allotransplantation (VCA) involves transplanting a functional and anatomically complete tissue graft, such as a hand or face, from a deceased donor to a recipient. Although clinical VCA has resulted in successful outcomes, high rates of acute rejection and increased requirements for immunosuppression have led to significant long-term complications. Of note, immunosuppressed graft recipients are predisposed to infections, organ dysfunction, and malignancies. The long-term success of VCA grafts requires the discovery and implementation of unique approaches that avoid these complications altogether. Here, we describe our surgical technique and initial experience with a reproducible heterotopic porcine VCA model for the preclinical assessment of approaches to improve graft outcomes.Methods Six heterotopic porcine allogeneic vertical rectus abdominis myocutaneous flap transplants were performed using Sinclair donors and Yucatan recipients. Immunosuppressive therapy was not used. Each flap was based on the left external iliac vessel system. Animals were followed postoperatively for surgery-related complications.Results The six pigs underwent successful VCA and were euthanized at the end of the study. Each flap demonstrated complete survival following vessel anastomosis. For the allogeneic recipients, on average, minimal erythema and healthy flap color were observed from postoperative days 1 to 4. There were no surgery-related animal deaths or complications.Conclusion We have developed a reproducible, technically feasible heterotopic porcine VCA model based on the left external iliac vessel system. Our results demonstrate this model's potential to improve VCA graft outcomes by exploring tolerance induction and rejection biomarker discovery in preclinical studies.
Keywords: vascularized composite allotransplantation; large animal model; swine; vertical rectus abdominis myocutaneous flap; external iliac vessels